Multicellular group formation in response to predators in the alga Chlorella vulgaris - Fisher,RM; Bell,T; West,SA (Journal of Evolutionary Biology, 2016)
A key step in the evolution of multicellular organisms is the formation of cooperative multicellular groups. It has been suggested that predation pressure may promote multicellular group formation in some algae and bacteria, with cells forming groups to lower their chance of being eaten. We use the green alga Chlorella vulgaris and the protist Tetrahymena thermophila to test whether predation pressure can initiate the formation of colonies. We found that: (1) either predators or just predator exoproducts promote colony formation; (2) higher predator densities cause more colonies to form; and (3) colony formation in this system is facultative, with populations returning to being unicellular when the predation pressure is removed. These results provide empirical support for the hypothesis that predation pressure promotes multicellular group formation. The speed of the reversion of populations to unicellularity suggests that this response is due to phenotypic plasticity and not evolutionary change.